1992
DOI: 10.1080/02640419208729924
|View full text |Cite
|
Sign up to set email alerts
|

Effect of induced alkalosis on swimming time trials

Abstract: Previous studies have shown that sodium bicarbonate ingestion prior to exercise may improve performance during repeated (interval) bouts. To examine the practical implications of such findings, seven collegiate swimmers participated in simulated swim competitions of multiple events following sodium bicarbonate (B) ingestion, placebo (P) ingestion and control (C--no ingestion) treatments. Each swimmer reported to the laboratory 1 h prior to the simulated competitions (72 h apart) and was randomly assigned to on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 7 publications
0
18
0
1
Order By: Relevance
“…These Wndings provide new information about the ergogenic eVects of NaHCO 3 and demonstrate that NaHCO 3 provides no beneWt to short-duration high-intensity swim performance in highly trained swimmers regardless of the loading protocol. Previous studies (Gao et al 1988;Mero et al 2004;Pierce et al 1992) have also failed to demonstrate improvements in swimming performance after acute loading of NaHCO 3 . However, these studies administered smaller doses, interval-swimming protocols and/or shorter swimming distances (e.g., 100 yd; 91.4 m).…”
Section: Discussionmentioning
confidence: 93%
“…These Wndings provide new information about the ergogenic eVects of NaHCO 3 and demonstrate that NaHCO 3 provides no beneWt to short-duration high-intensity swim performance in highly trained swimmers regardless of the loading protocol. Previous studies (Gao et al 1988;Mero et al 2004;Pierce et al 1992) have also failed to demonstrate improvements in swimming performance after acute loading of NaHCO 3 . However, these studies administered smaller doses, interval-swimming protocols and/or shorter swimming distances (e.g., 100 yd; 91.4 m).…”
Section: Discussionmentioning
confidence: 93%
“…Subsequent investigations largely, though not always, confirmed these early findings in various repeated swim models (Mero et al;2004;Pruscino et al, 2008;Siegler & Gleadall-Siddall, 2010;Zajac et al, 2009), though Zajac et al (2009) found significant performance improvement only in the first of four 50-m swims. Pierce et al (1992) looked at the effects of supplementation in simulated swim competitions involving one 91.4-m swim followed by two 182.8-m swims with a 20-min recovery between each and found no effect on performance. An increased speed in the later swims of a set of intervals may be seen as providing a greater stimulus to training adaptation, but blunting of the metabolic acidosis may reduce the adaptation.…”
Section: Bicarbonate and Beta-alaninementioning
confidence: 99%
“…Some studies have examined the ergogenic potential of SB on short-distance swimming performance (i.e., 100 and 200 m or 100 and 200 yards) and interval swimming performance (Gao et al 1988;Pierce et al 1992;Lindh et al 2008;Pruscino et al 2008;Siegler and Hirscher 2010;Joyce et al 2012). However, results are quite conflicting; some studies reported no effect of SB on timetrial performance (Pierce et al 1992;Pruscino et al 2008;Joyce et al 2012), one reported a positive effect on swimming trials (Lindh et al 2008), and others reported improved interval swimming performance (Gao et al 1988;Siegler and Hirscher 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, results are quite conflicting; some studies reported no effect of SB on timetrial performance (Pierce et al 1992;Pruscino et al 2008;Joyce et al 2012), one reported a positive effect on swimming trials (Lindh et al 2008), and others reported improved interval swimming performance (Gao et al 1988;Siegler and Hirscher 2010). However, no study has yet investigated the effects of BA supplementation on swimming performance.…”
Section: Introductionmentioning
confidence: 99%